Clinical genetics of spondylocostal dysostosis: A mini review - Umair, Muhammad; Younus, Muhammad; Shafiq, Sarfraz; Nayab, Anam; Alfadhel, Majid (Frontiers in Genetics, 2022)
Spondylocostal dysostosis is a genetic defect associated with severe rib and vertebrae malformations. In recent years, extensive clinical and molecular diagnosis advancements enabled us to identify disease-causing variants in different genes for such severe conditions. The identification of novel candidate genes enabled us to understand the developmental biology and molecular and cellular mechanisms involved in the etiology of these rare diseases. Here, we discuss the clinical and molecular targets associated with spondylocostal dysostosis, including clinical evaluation, genes, and pathways involved. This review might help us understand the basics of such a severe disorder, which might help in proper clinical characterization and help in future therapeutic strategies.